The rise and fall of the great powers : - Kennedy, Paul M. (Unwin, 1988)
About national and international power in the "modern" or Post Renaissance period. Explains how the various powers have risen and fallen over the 5 centuries since the formation of the "new monarchies" in W. Europe.